U.S. Military Courts and the War in Iraq - Frank, Michael J. (2006)
Throughout its history, the United States has frequently entrusted to military courts the task of prosecuting insurgents and terrorists during instances of military occupation. Instead of carrying on this tradition in Iraq, the United States created the Central Criminal Court of Iraq (CCCI) and entrusted a band of Iraqi judges with this task. Infected with corruption, nationalism, tribal loyalties, and anti-U.S. animus, this court has repeatedly thwarted the United States by acquitting or only lightly punishing Iraqi terrorists. Thus, the terrorists have learned that they face an excellent chance of acquittal in the CCCI, or if per chance they are convicted, they must simply bide their time until their short sentences have expired, at which point they will be free to kill again. This Article discusses the numerous problems engendered by the CCCI and proposes a return to the tradition of using military courts. It demonstrates the superiority of U.S. military courts and the advantages they would entail, including major gains toward winning the war in Iraq